Data Mining: A Necessity For Information Security - Bhatnagar, Vishal; Sharma, Sanur (Journal of Knowledge Management Practice, 2012)
In today’s digital age security of information is of utmost importance. With petabytes of data floating around, it becomes essential that only the authorized users have access to it. With the increasing amount of information, Data Mining has become a significant resource for information security. Data mining provides the best applicable technique, according to the different information security areas, for achieving a desired level of privacy. In this paper we have identified the different emerging areas of information security and the various data mining techniques that can be applied in those areas to mitigate the rising security risks and threats.